Virtual reality and animation for MATLAB and simulink users : visualization of dynamic models and control simulations - Khaled, Nassim (Springer, 2012)
This book demonstrates the simulation and animation of physical systems using the MATLAB(R) Virtual Reality Toolbox. Taking a problem-based approach, each chapter teaches a group of essential principles, following a step-by-step solution to a particular issue